FETUSES LOSSES IN SMALL RUMINANTS: A CASE STUDY OF HADEJIA EMIRATE COUNCIL OF JIGAWA STATE. - Nasir, M.; Aliyu, A. M.; Bature, I. (FUDMA JOURNAL OF SCIENCES, 2021)
A study was conducted to assess the extent of foetal losses from small ruminants and possible factors responsible for slaughtering female animals in semi-arid abattoirs of Hadejia and Malam-Madori, Jigawa State. The study was carried out using structured questionnaire administered to 160 respondents in the abattoirs for a period of three months (June-August, 2013). Specify the statistical tool you used to analyzed your results here. The results revealed that youths aged less than 25 (35.71%) and 36-45 (37.29%) years were the main source of labour in Hadejia and Malam-Madori.The respondents were mostly engaged in evisceration and skinning (75.71% and 82.86%) in the abattoirs. Majority (77.15% and 72.00%) of the respondents in both study areas were males, mostly (68.00% and 60.00%) married, few (12.00% and 9.33%) had tertiary education, while many (26.67% and 32.00%) had acquired secondary education. Small ruminant foetuses recovered from 6 to 10 per day were 65.71% and 52.85% which vary with season. It was concluded that there was a cause for concern on loss of fetuses especially among small ruminants. It is therefore suggested that awareness should be created among livestock rearers/farmers and butchers on the implication of slaughtering of pregnant animals and its consequence on the future of small ruminant’s population since increase in population of any livestock species is based on reproduction. Thus, legislation prohibiting indiscriminate slaughter of pregnant or inbred female animals should be enforced or enacted as this has far reaching negative impact on reproduction/production and revenue generation in